Epidemiological profile of elderly brazilians seeking physical therapy treatment: a literature review - Costa, Adiele Sousa da (2021)
The aging process occurs during life, affecting all organisms, being considered progressively causing several changes in the individual's physiological patterns, involving social, cultural, biological and psychological factors. Physical therapy may be necessary at any stage of life, but for the elderly population it is essential not only related to treatment, but preventive, contributing to a better quality of life. Thus, it is extremely important to identify the profile of patients seen in a given population, know the users of the physiotherapy service, understand the service demand, and the most frequent pathologies. This is a descriptive exploratory literature review, a method by which a topic studied in previous research is narrated in detail, in order to cover more about a given subject. The search was carried out in the following healthcare databases: Academic Google, Latin American and Caribbean Health Sciences Literature (LILACS) and Scientific Electronic Library Online (SciELO). In this research, it was possible to observe a growing search for physiotherapeutic care in several areas of activity, and the predominance of patients seen was female over 60 years of age. Another important fact observed in the research was the fact that patients did not have only one diagnosis, but several comorbidities, decreasing the functional capacity of the elderly, causing deleterious effects on their quality of life, it is noteworthy that the need for more frequent care by physical therapists was caused by muscle disorders representing 83% of cases and neurological disorders with 61.1% of searches for assistance.